Strength, shrinkage and creep of lightweight cementitious composite incorporating carbon nanofibers - Wang, Su (2022)
This work evaluates the potential use of a new foam concrete design for structural applications resulting from ultra-high performance concrete mix design by incorporating homogeneous micro-foam to create a lightweight cementitious composite (LCC). The fresh and mechanical properties of LCC were studied with a density ranging from 800 to 1700 kg/m3. Results showed that the strength development of LCC with increasing density was much greater than that of conventional foam concrete. New strength equations were proposed to describe the relationship among density, compressive strength and flexural strength of LCC in comparison to well-established concrete equations in the ACI code and published literature. Based on the experimental results, LCC with a density of 1500 kg/m3 (LCC-1500) was selected for further investigation because of its high strength-to-density ratio, and carbon nanofibers (CNFs) were incorporated to produce CNF-LCC-1500 to study the mechanical properties and long-term properties including shrinkage and creep behaviour. Generally, CNF-LCC-1500 exhibited equivalent or even better performance in both short- and long-term properties than normal-weight concrete and lightweight concrete with similar compressive strength. In addition, a hyperbolic equation was applied to predict the creep development with ages of CNF-LCC-1500. Furthermore, CNFs could effectively improve both short- and long-term properties due to the optimized nano- and micropore structure.